EXPRESSION OF RELIGION AND CULTURE OF KASEPUHAN CISUNGSANG CUSTOMARY COMMUNITY AT A PROCESSION OF PANTUN RECITATION OF RADEN GALUH PAKUAN PAJAJARAN IN THE SEREN TAUN CEREMONY - Mahmudah Nur (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
Traditional pantun is one of series of events that still carried out in the Seren Taun ceremony in the Kasepuhan Cisungsang customary community. Pantun has a very important function for the customary community of Banten in particular and the Sundanese in general, which as a medium of communication, traditional knowledge of customary community, and a means of ritual as well. This study identified the forms of religious and cultural expressions in the traditional pantun tradition. This descriptive study employed qualitative data which aims to describe the form of acculturation of religion and culture in the pantun tradition. The folklore approach was used to analyze the story of pantun which is the focus of the discussion and related it to the cultural background of the Kasepuhan Cisungsang customary community. This study shows that the procession series of Seren Taun ceremony in Kasepuhan Cisungsang, plays a very important role in integrating the complex differences of view among modern society. Traditional pantun in a series of Seren Taun events become a source of knowledge and cultural expression of Kasepuhan Cisungsang customary community in order to maintain their traditions. The story of the RGPP pantun developed in the Cisungsang customary community is a real picture of their cosmology of life harmony with the natural environments, social and cultural environment.